Meta-Analysis of Guru Penggerak and Kurikulum Merdeka Initiatives in Enhancing Education Quality in Indonesia - Usman Jayadi; Latifatul Isro'iyah (International Journal of Education and Digital Learning (IJEDL), 2025)
This study explores the significant role of Guru Penggerak and the Kurikulum Merdeka in enhancing educational quality in Indonesia. The research aims to assess how these initiatives improve teaching practices and student outcomes. Employing a Meta-Analysis Literature Review (MALR), the study systematically combines findings from various studies using statistical methods. Data analysis reveals that Guru Penggerak's active involvement in professional development and curriculum innovation, alongside the flexible, student-centered Kurikulum Merdeka, significantly improve educational quality. The research highlights the synergy between these initiatives, providing substantial theoretical and practical contributions. Limitations include reliance on secondary data and suggest future research on long-term impacts and stakeholder perspectives. The study underscores the critical importance of teacher empowerment and curriculum flexibility in driving systemic educational improvements.